A cohort study of feeding patterns and health outcomes of infants in the Rufiji district of Tanzania - Elisaria, Ester (Curtin University, 2015)
A mother-infant pair cohort study with 1302 participants was undertaken in the Rufiji district of rural Tanzania. Almost all infants (99%) were breastfed but only 2% were exclusively breastfed until six months of age. Lower maternal and paternal education levels, the use of pre-lacteal feeds, religion and maternal ownership of a radio were associated with exclusive breastfeeding. There was no statistical significant difference in growth and infection rates between exclusively and non-exclusively breastfed infants.